Logging evaluation method for organic geochemical parameters of shale in Jurassic Formation - Gan, Renzhong; Zhang, Hao; Fang, Tao; Mu, Liwei; Ni, Liping; Chai, Lixue (Frontiers in Earth Science, 2025)
Black shale is the main source rock of the Jurassic Liangshan Formation shale reservoir in basin A, and its organic geochemical parameters TOC, S1, and S2 are very important for the quantitative evaluation of shale reservoir exploration and development potential. TOC, S1, and S2 logging evaluation methods are established according to the principle of “core calibration logging” because of the possession of logging and core analysis data in basin A. Firstly, improved △logR and multiple regression analysis methods are used to establish a quantitative TOC logging method based on slowness, resistivity, and gamma-ray logging. Secondly, based on acoustic time difference, resistivity, and gamma logging, a quantitative calculation method of S2 is established by multiple regression analysis. Finally, based on the statistical relationship between TOC and (S1+S2) of core analysis and S2 calculation results, a logging method for quantitative calculation of S1 is obtained. The application results show that the TOC calculated based on multiple regression analysis is in good agreement with the TOC of core analysis, with A relative deviation of 9%. The modified △logR method results in a large deviation from the TOC of core analysis due to the influence of the error of coefficient A and overlap coefficient K. The relative deviation of S1 and S2 calculated by logging and S1 and S2 by core analysis is 6% and 7%, which can meet the evaluation requirements of hydrocarbon generation potential of source rocks.